A nano material doped molybdenum alloy material and preparation method thereof
By performing nanomaterial doping treatment on molybdenum metal materials, the problem of high-end utilization caused by the gap in molybdenum metal processing technology is solved, the mechanical properties of molybdenum alloy materials are improved, and the problem of insufficient strength of molybdenum metal materials in the existing technology is solved.
Patent Information
- Application Number
- CN202411245239.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-06
AI Technical Summary
There is a big gap between my country's molybdenum metal processing technology and international advanced processes, resulting in high-end molybdenum metal products need to be imported from abroad and the high-end utilization of molybdenum metal materials needs to be improved.
The preparation method of nanomaterial doped molybdenum alloy material is adopted, and TiC and Y2O3 materials are modified and mixed with ammonium molybdate heptahydrate, and reduced through two steps: lyophilization and hydrogen, and finally sintered at high temperature. The nanomaterial doped molybdenum alloy material is formed to inhibit carbide grain growth and grain boundary migration, refine molybdenum metal grains, and improve its mechanical properties.
The reaction between TiC and the carbon element introduced by the surface modification of yttrium oxide and the molybdenum metal material is effectively inhibited, the grain boundary migration is hindered, the grain size of molybdenum metal is refined, and the strength and mechanical properties of molybdenum alloy are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molybdenum alloys, and in particular to a nano material-doped molybdenum alloy material and a preparation method thereof. Background Art
[0002] Molybdenum metal is an important metal material with advantages such as high melting point, low thermal expansion coefficient and high thermal conductivity. It has extremely important strategic value in aerospace and nuclear industries. However, at present, there is still a large gap between my country's molybdenum metal processing technology and international advanced technology. Although my country has huge molybdenum metal deposits, the main molybdenum metal industry is primary processing and smelting. High-end molybdenum metal products still need to be imported from abroad to meet demand. Therefore, it is necessary to conduct research on the processing technology of molybdenum metal to enhance the high-end utilization of molybdenum metal materials. Summary of the invention
[0003] The object of the present invention is to provide a nanomaterial-doped molybdenum alloy material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0005] S1. Preparation of modified nanomaterials;
[0006] After grinding TiC particles to 80-200 nm, disperse them in ultrapure water, and disperse them under ultrasonic vibration for 1-3 hours in a nitrogen environment, add γ-aminopropyltriethoxysilane, heat to 80-95° C., reflux and stir to react for 8-12 hours, centrifuge and separate the precipitate, wash with distilled water 2-3 times, and vacuum evaporate to constant weight to obtain amino-modified TiC material;
[0007] S12. After grinding Y2O3 to 400-800nm, γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4-8h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0008] S13. The amino-modified TiC material and the epoxy-modified Y2O3 material are dispersed in distilled water respectively, and ultrasonically dispersed for 1-2 hours under a nitrogen atmosphere, and then the two dispersions are mixed, and the temperature is raised to 75-80°C under a nitrogen atmosphere, and refluxed for 8-12 hours. After centrifugal separation and precipitation, the obtained precipitate is ball-milled again for 4-8 hours, and then discharged to obtain a modified nanomaterial;
[0009] S2. Ammonium molybdate heptahydrate was dissolved in distilled water, ammonia was added to adjust the pH value to 8.5-9, the modified nanomaterial was added, ultrasonically mixed for 4-8h, the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0010] S3. The precursor powder is placed in an air atmosphere, heated to 450-600°C, calcined for 0.5-1.8h, the calcined powder is collected, placed in a hydrogen atmosphere, and reduced in two steps to obtain a composite reduced molybdenum powder;
[0011] S4. After cold isostatic pressing of the composite reduced molybdenum powder, the composite reduced molybdenum powder is placed in a hydrogen atmosphere again, calcined for 3-6 hours, and then cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0012] Furthermore, in step S11, the mass ratio of the TiC particles to γ-aminopropyltriethoxysilane is 10:(0.5-4).
[0013] Furthermore, in step S12, the mass ratio of Y2O3 to γ-glycidyloxypropyltrimethoxysilane is 10:(0.1-0.3).
[0014] Furthermore, in step S13, the mass ratio of the amino-modified TiC material to the epoxy-modified Y2O3 material is (0.1-0.8): (1.5-3).
[0015] Furthermore, in step S2, the mass ratio of the ammonium molybdate heptahydrate to the modified nanomaterial is 191:(1.6-3.8) in parts by weight.
[0016] Furthermore, in step S3, during the two-step reduction, the temperature is first raised to 600-680°C and calcined for 1-2 hours in a hydrogen atmosphere; then the temperature is raised to 800-850°C and calcined for 1.5-2 hours in a hydrogen atmosphere.
[0017] Furthermore, in step S4, during the cold isostatic pressing, the pressure is 150-200 MPa.
[0018] Furthermore, in step S4, the calcination temperature is 1550-1650°C.
[0019] Furthermore, a nanomaterial-doped molybdenum alloy material is prepared by the above method.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] In order to improve the performance of the prepared molybdenum alloy material, the present invention uses TiC and yttrium oxide as reinforcing materials and modifies them, thereby achieving the reinforcement of the molybdenum alloy;
[0022] The present invention first limits the particle sizes of TiC and yttrium oxide materials, prepares them into particles of 80-200nm and 400-800nm respectively, and on this basis, uses γ-aminopropyltriethoxysilane to modify the TiC material, grafts amino groups on the surface of the TiC material, and then uses γ-glycidyloxypropyltrimethoxysilane to modify the yttrium oxide material, so that after epoxy groups are introduced on the surface of the yttrium oxide, the modified TiC material is mixed with the yttrium oxide material, and the reaction between the amino groups and the epoxy groups is utilized to coat the TiC material with a smaller particle size on the surface of the yttrium oxide; at the same time, in order to avoid the cross-linked network formed when the TiC material is used to coat the surface of the yttrium oxide causing the particle size of the modified nano material to be too large, the present invention also performs a re-grinding treatment on the TiC material to avoid the reinforcement material with too large particle size from forming defects in the molybdenum metal material matrix;
[0023] Then, the modified nano material after grinding is dispersed in an ammonium molybdate heptahydrate solution, and after freeze-drying, a loose precursor powder in which the modified nano material is evenly dispersed is formed, and the precursor powder is placed in an air atmosphere and reduced in two steps by hydrogen to form a composite reduced molybdenum powder; then, the precursor powder is pressed and sintered, and under the action of high temperature, TiC in the modified nano material prepared by the present invention will adsorb oxygen impurities in the molybdenum matrix and yttrium oxide, and generate a TiO2 phase in this process, clean the grain boundary and pin the dislocation, and can effectively inhibit the reaction between the carbon element introduced by the surface modification of TiC and yttrium oxide and the molybdenum metal material, effectively inhibit the growth of carbide grains therein, hinder the migration of grain boundaries, and refine the grain size of the molybdenum metal, thereby improving the strength of the molybdenum alloy and making it have more excellent mechanical properties. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0026] S1. Preparation of modified nanomaterials;
[0027] By weight, 10 parts of TiC particles were ground into 80-200 nm, dispersed into ultrapure water, and dispersed under ultrasonic vibration for 1 hour in a nitrogen environment. Then, 0.5 parts of γ-aminopropyltriethoxysilane were added thereto, the temperature was raised to 80° C., refluxed and stirred for 8 hours, and the precipitate was separated by centrifugation. After washing with distilled water twice, the precipitate was evaporated in vacuum to constant weight to obtain an amino-modified TiC material.
[0028] S12. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0029] S13. By weight, 0.1 parts of amino-modified TiC material and 1.5 parts of epoxy-modified Y2O3 material were dispersed in distilled water, respectively, and ultrasonically dispersed for 2 hours under a nitrogen atmosphere. The two dispersions were mixed, heated to 75°C under a nitrogen atmosphere, refluxed for 12 hours, centrifuged and precipitated, and the resulting precipitate was ball-milled again for 8 hours before discharging to obtain a modified nanomaterial;
[0030] S2. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH to 8.5, 1.6 parts of modified nanomaterials were added, ultrasonically mixed for 4 hours, the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0031] S3. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, the calcined powder was collected, placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0032] S4. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0033] Example 2. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0034] Compared with Example 1, this example increases the amount of γ-aminopropyltriethoxysilane added in step S1;
[0035] S1. Preparation of modified nanomaterials;
[0036] By weight, 10 parts of TiC particles were ground into 80-200 nm, dispersed into ultrapure water, dispersed under ultrasonic vibration for 1 hour in a nitrogen environment, and then 4 parts of γ-aminopropyltriethoxysilane were added thereto. The temperature was raised to 80° C., refluxed and stirred for 8 hours, and then centrifuged to separate the precipitate. After washing twice with distilled water, the precipitate was evaporated in vacuum to constant weight to obtain an amino-modified TiC material.
[0037] S12. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0038] S13. By weight, 0.1 parts of amino-modified TiC material and 1.5 parts of epoxy-modified Y2O3 material were dispersed in distilled water, respectively, and ultrasonically dispersed for 2 hours under a nitrogen atmosphere. The two dispersions were mixed, heated to 75°C under a nitrogen atmosphere, refluxed for 12 hours, centrifuged and precipitated, and the resulting precipitate was ball-milled again for 8 hours before discharging to obtain a modified nanomaterial;
[0039] S2. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH to 8.5, 1.6 parts of modified nanomaterials were added, ultrasonically mixed for 4 hours, the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0040] S3. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, the calcined powder was collected, placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0041] S4. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0042] Example 3. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0043] Compared with Example 1, this example increases the amount of amino-modified TiC added in step S13;
[0044] S1. Preparation of modified nanomaterials;
[0045] By weight, 10 parts of TiC particles were ground into 80-200 nm, dispersed into ultrapure water, and dispersed under ultrasonic vibration for 1 hour in a nitrogen environment. Then, 0.5 parts of γ-aminopropyltriethoxysilane were added thereto, the temperature was raised to 80° C., refluxed and stirred for 8 hours, and the precipitate was separated by centrifugation. After washing with distilled water twice, the precipitate was evaporated in vacuum to constant weight to obtain an amino-modified TiC material.
[0046] S12. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0047] S13. By weight, 0.8 parts of amino-modified TiC material and 1.5 parts of epoxy-modified Y2O3 material were dispersed in distilled water, respectively, and ultrasonically dispersed for 2 hours under a nitrogen atmosphere. The two dispersions were mixed, heated to 75°C under a nitrogen atmosphere, refluxed for 12 hours, centrifuged and precipitated, and the resulting precipitate was ball-milled again for 8 hours before discharging to obtain a modified nanomaterial;
[0048] S2. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH to 8.5, 2.3 parts of modified nanomaterials were added, ultrasonically mixed for 4 hours, the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0049] S3. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, the calcined powder was collected, placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0050] S4. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0051] Example 4. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0052] Compared with Example 1, this example increases the amount of epoxy-modified Y2O3 added in step S13;
[0053] S1. Preparation of modified nanomaterials;
[0054] By weight, 10 parts of TiC particles were ground into 80-200 nm, dispersed into ultrapure water, and dispersed under ultrasonic vibration for 1 hour in a nitrogen environment. Then, 0.5 parts of γ-aminopropyltriethoxysilane were added thereto, the temperature was raised to 80° C., refluxed and stirred for 8 hours, and the precipitate was separated by centrifugation. After washing with distilled water twice, the precipitate was evaporated in vacuum to constant weight to obtain an amino-modified TiC material.
[0055] S12. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0056] S13. Disperse 0.1 parts of amino-modified TiC material and 3 parts of epoxy-modified Y2O3 material in distilled water by weight, disperse them by ultrasonic dispersion for 2 hours under nitrogen atmosphere, mix the two dispersions, heat them to 75°C under nitrogen atmosphere, reflux for 12 hours, centrifuge and precipitate, ball-mill the precipitate again for 8 hours, and then discharge the mixture to obtain a modified nanomaterial;
[0057] S2. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH to 8.5, 3.1 parts of modified nanomaterials were added, and ultrasonic mixing was performed for 4 hours. The mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0058] S3. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, the calcined powder was collected, placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0059] S4. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0060] Comparative Example 1. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0061] Compared with Example 1, this comparative example only added ground TiC particles and Y2O3 materials respectively;
[0062] S1. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH value to 8.5, 0.1 parts of TiC material with a particle size of 80-200nm and 1.5 parts of Y2O3 material with a particle size of 400-800nm were added, and ultrasonic mixing was performed for 4h, and the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0063] S2. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, and the calcined powder was collected and placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0064] S3. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0065] Comparative Example 2. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0066] Compared with Example 1, this comparative example does not use ammonium molybdate heptahydrate, but directly uses molybdenum powder mixed with modified nanomaterials;
[0067] S1. Preparation of modified nanomaterials;
[0068] By weight, 10 parts of TiC particles were ground into 80-200 nm, dispersed into ultrapure water, and dispersed under ultrasonic vibration for 1 hour in a nitrogen environment. Then, 0.5 parts of γ-aminopropyltriethoxysilane were added thereto, the temperature was raised to 80° C., refluxed and stirred for 8 hours, and the precipitate was separated by centrifugation. After washing with distilled water twice, the precipitate was evaporated in vacuum to constant weight to obtain an amino-modified TiC material.
[0069] S12. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0070] S13. By weight, 0.1 parts of amino-modified TiC material and 1.5 parts of epoxy-modified Y2O3 material were dispersed in distilled water, respectively, and ultrasonically dispersed for 2 hours under a nitrogen atmosphere. The two dispersions were mixed, heated to 75°C under a nitrogen atmosphere, refluxed for 12 hours, centrifuged and precipitated, and the resulting precipitate was ball-milled again for 8 hours before discharging to obtain a modified nanomaterial;
[0071] S2. By weight, 1.6 parts of modified nanomaterials were added to 100 parts of molybdenum powder, and stirred for 4h to obtain a precursor powder;
[0072] S3. After the precursor powder is pressed into shape by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and then cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0073] Comparative Example 3. A method for preparing a nanomaterial-doped molybdenum alloy material, comprising the following steps:
[0074] Compared with Example 1, this comparative example only adds and prepares epoxy-modified Y2O3 material to replace the modified nanomaterial;
[0075] S1. After grinding 10 parts of Y2O3 to 400-800nm by weight, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane were added thereto, and ball milling was continued for 4h, and the material was cooled to obtain an epoxy-modified Y2O3 material;
[0076] S2. By weight, 191 parts of ammonium molybdate heptahydrate were dissolved in distilled water, ammonia was added to adjust the pH value to 8.5, 1.6 parts of epoxy-modified Y2O3 material were added, and ultrasonic mixing was performed for 4 hours. The mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder;
[0077] S3. The precursor powder was placed in an air atmosphere, heated to 500 ° C, calcined for 1.8 hours, the calcined powder was collected, placed in a hydrogen atmosphere, heated to 600 ° C, calcined for 2 hours in a hydrogen atmosphere, and then heated to 800 ° C, calcined and reduced in a hydrogen atmosphere for 1.5 hours to obtain a composite reduced molybdenum powder;
[0078] S4. After the composite reduced molybdenum powder is pressed by cold isostatic pressing at a pressure of 180 MPa, it is placed in a hydrogen atmosphere again, heated to 1600° C., calcined for 3 hours, and cooled to obtain a nanomaterial-doped molybdenum alloy material.
[0079] Testing: The surfaces of the nanomaterial-doped molybdenum alloy materials prepared in Examples 1-4 and Comparative Examples 1-3 were polished, and a load of 200 gf was applied to the surfaces for 20 seconds to perform Vickers hardness testing;
[0080] According to GB / T 228.1-221, the tensile strength of the nanomaterial-doped molybdenum alloy materials prepared in Examples 1-4 and Comparative Examples 1-3 was tested, and the test results are shown in the following table;
[0081]
[0082] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanomaterial-doped molybdenum alloy material, characterized in that: The following steps are involved: S1. Preparation of modified nanomaterials; After grinding TiC particles to 80-200 nm, disperse them in ultrapure water, and disperse them under ultrasonic vibration for 1-3 hours in a nitrogen environment, add γ-aminopropyltriethoxysilane, heat to 80-95° C., reflux and stir to react for 8-12 hours, centrifuge and separate the precipitate, wash with distilled water 2-3 times, and vacuum evaporate to constant weight to obtain amino-modified TiC material; Wherein, the mass ratio of the TiC particles to γ-aminopropyltriethoxysilane is 10:(0.5-4); S12. After grinding Y2O3 to 400-800nm, γ-glycidyloxypropyltrimethoxysilane was added thereto, and ball milling was continued for 4-8h, and the material was cooled to obtain an epoxy-modified Y2O3 material; Wherein, the mass ratio of Y2O3 and γ-glycidyloxypropyltrimethoxysilane is 10:(0.1-0.3); S13. The amino-modified TiC material and the epoxy-modified Y2O3 material are dispersed in distilled water respectively, and ultrasonically dispersed for 1-2 hours under a nitrogen atmosphere, and then the two dispersions are mixed, and the temperature is raised to 75-80°C under a nitrogen atmosphere, and refluxed for 8-12 hours. After centrifugal separation and precipitation, the obtained precipitate is ball-milled again for 4-8 hours, and then discharged to obtain a modified nanomaterial; Wherein, the mass ratio of the amino-modified TiC material to the epoxy-modified Y2O3 material is (0.1-0.8): (1.5-3); S2. Ammonium molybdate heptahydrate was dissolved in distilled water, ammonia was added to adjust the pH value to 8.5-9, the modified nanomaterial was added, ultrasonically mixed for 4-8h, the mixture was poured into liquid nitrogen and frozen, and then added to a freeze dryer to remove moisture to obtain a precursor powder; S3. The precursor powder is placed in an air atmosphere, heated to 450-600°C, calcined for 0.5-1.8h, the calcined powder is collected, placed in a hydrogen atmosphere, and reduced in two steps to obtain a composite reduced molybdenum powder; S4. After cold isostatic pressing of the composite reduced molybdenum powder, the composite reduced molybdenum powder is placed in a hydrogen atmosphere again, calcined for 3-6 hours, and then cooled to obtain a nanomaterial-doped molybdenum alloy material.
2. The method for preparing a nanomaterial-doped molybdenum alloy material according to claim 1, characterized in that: In step S2, the mass ratio of the ammonium molybdate heptahydrate to the modified nanomaterial is 191:(1.6-3.8) in parts by weight.
3. The method for preparing a nanomaterial-doped molybdenum alloy material according to claim 1, characterized in that: In step S3, during the two-step reduction, the temperature is first raised to 600-680° C. and calcined for 1-2 h in a hydrogen atmosphere; then the temperature is raised to 800-850° C. and calcined and reduced for 1.5-2 h in a hydrogen atmosphere.
4. The method for preparing a nanomaterial-doped molybdenum alloy material according to claim 1, characterized in that: In step S4, during the cold isostatic pressing, the pressure is 150-200 MPa.
5. The method for preparing a nanomaterial-doped molybdenum alloy material according to claim 1, characterized in that: In step S4, the calcination temperature is 1550-1650°C.
6. A nanomaterial-doped molybdenum alloy material prepared by the preparation method according to any one of claims 1 to 5.
